Biokonversi Sampah Organik Kulit Pisang Menggunakan Larva Black Soldier Fly (BSF) - Mufti, Aulia Annas; Thessalonika, Sheren; Mawaddah, Nurul (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2024)
Waste is goods considered unused and thrown away by the previous owner/user, but under certain conditions and processing the waste can still be used. An example is organic waste, organic waste is waste that can undergo weathering or what is usually called decomposition and break down into smaller, odorless materials. This research aims to analyze the effect of feeding rate on larval nutritional quality, residue yield quality and banana peel waste reduction index using the bioconversion method. Bioconversion is a waste processing process that involves microorganisms to convert organic waste into products that have market value. This research used Black Soldier Fly (BSF) larvae as a bioconverter for selected organic waste, namely banana peel waste. The variables used in this study consisted of variations in the number of different feeding rates with 4 variations, namely 40, 60, 80 and 100 mg/larva/day for 15 days, where each variation was given 3 containers and each container contained 2000 BSF larvae. The research results that will be obtained are environmental conditions during the bioconversion process and the value of the waste reduction index or WRI.